Early Second‐Trimester Sonography to Improve the Fetal Anatomic Survey in Obese Patients. (1st September 2014) - Gupta, Simi; Timor-Tritsch, Ilan E.; Oh, Cheongeun; Chervenak, Judith; Monteagudo, Ana
Abstract : Objectives: Fetal anatomic surveys are difficult to perform on obese patients. However, there are limited data available on methods to improve the rate of complete anatomy scans in these patients. The objective of this study was to determine whether the addition of an early second‐trimester fetal anatomy scan improves the rate of complete anatomy scans in obese patients. Methods: We conducted a prospective cohort study of 100 obese patients at a city hospital who were scheduled for a fetal anatomy scan using transvaginal and transabdominal sonography at 14 to 16 weeks (early anatomy scan) and an anatomy scan at 18 to 22 weeks ("routine" anatomy scan). Inclusion criteria were a body mass index of 30 kg/m 2 or higher, singleton pregnancy, and presentation for prenatal care before 16 weeks. Data for the routine anatomy scan alone versus a combination of early and routine anatomy scans was calculated by the McNemar χ 2 test for categorical variables and the Wilcoxon signed ranks test for continuous variables. Results: The addition of the early anatomy scan significantly increased the rate of complete anatomy scans from 42% to 51% ( P < .01). It also significantly improved visualization of the head, thorax, and abdomen and significantly increased the mean number of items seen ( P < .05). Conclusions: The addition of an early second‐trimester fetal anatomy scan to a routine anatomy scan performed later in the second trimester significantly improves the rate of complete anatomy scans in obese patients.